SMOKE SIGNALS - COLLINS,L; CONNER,C; FRIEND,T; MARTINDALE,D; SHARN,L (Tufts Archival Research Center, 2007)
Two different news articles describing the battle surrounding the smoking ban on all domestic flights, two hours or less. Describes the Association of Flight Attendants’ desire for a smoking ban on flights of all lengths. Cites studies showing the danger of second hand smoke on an airplane with re-circulating air and specifically mentions the Environmental Protection Agency’s (EPA) most recent report on second-hand smoke in the workplace. Presents the people and organizations on either side of the debate for total in-flight smoking restriction.